Computational Thinking Game Design Based on the Bebras Challenge: A Controlled Experiment - Laisa, Jéssica; Henrique, Eduardo (Anais do Workshop sobre Educação em Computação (WEI); 2022: Anais do XXX Workshop sobre Educação em Computação, 2022)
The use of games is a promising approach to engage students and to teach computational few educational games are related to this topic. One reason for that is the difficult to create CT Game Designs. In this context, this work has the objective of verifying if interesting computational thinking games can be created from the analysis of Bebras Challenge tasks, an international initiative that presents a set of attractive and well-elaborated tasks to exercise and evaluate computational thinking (CT) abilities. A controlled experiment was performed and the achieved results indicate that Bebras tasks are a good source of inspiration for designing CT games. Hence, their use can support the creation of new CT games, ensuring a balanced level of educational and entertainment aspects.